Implementation relationship of occupational activity based on Balinese culture towards increasing elderly cognitive - Sudiantara,, Ketut (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to know the relationship of Balinese culture-based occupational therapy to cognitive improvement in the elderly in Gianyar Regency 2019. Cognitive defined as what was known and thought by someone. It was classically interpreted as a high-level mental process. It makes humans aware of objects then able to remember them, make classifications, concepts, symbols, and solve problems in response to objects, or stimuli. This type of research was a randomized pretest and posttest control group design. It used a multistage random method with 215 samples. Data analysis techniques used univariate and chi-square analysis. Univariate was used to determine the distribution of the observed variables. Chi-Square was used to determine the therapeutic relationship of each occupational activity to cognitive changes. The results showed the variable of cultural activity had a relationship to the prevention of dementia was only dancing and sewing with constants values, respectively 2,027 and 2,266. Whereas, Constanta of all other variables was - 5,344. Based on these results the elderly are expected to continue to practice based on hobbies. Therefore, the process of the cognitive decrease can be reduced.